Empirical analysis of international collaboration in the provision of Defence assets: Advantages and Limitations - García Peña, Santiago (Journal of the Spanish Institute for Strategic Studies, 2021)
Despite the fact that collaboration in european armaments programs has more than seventy years, the difficulties for such collaboration persist. Mainly, it can be highlighted the harmonization of requirements and the achievement of consensus, motivated by national interests and preferences and budgetary priorities that do not match with those of the potential partners. Through the study of potential advantages and main drawbacks present in international collaboration programs, together with the analysis of cases of success and failure in Europe, it is concluded that this collaboration allows strengthening international security and defence relations, sharing risks, efforts and resources in obtaining new, more advanced common capabilities that improve interoperability among allies. This can also act as a catalyst for an industrial restructuring that streamlines the number of main contractor companies, encourages specialization and improves their international competitiveness.